Experimental and numerical investigation of an advanced injection cooling concept for Organic Rankine Cycles. (15th November 2020) - Eyerer, Sebastian; Dawo, Fabian; Pili, Roberto; Schifflechner, Christopher; Wieland, Christoph; Spliethoff, Hartmut
Graphical abstract: Highlights: Injection of liquid working fluid into the exhaust vapor line of an ORC system. Injection effectively desuperheats the vapor and increases the condenser heat transfer. In new built systems, smaller heat exchanger surfaces are sufficient. In existing systems, the injection cooling leads to up to 7.9 kW higher net power output. Abstract: The present experimental and numerical investigation is about an efficiency increasing and/or cost-reducing measure for Organic Rankine Cycle (ORC) systems. In such systems, a high proportion of the self-consumption of the system lies in the condensation of the working fluid due to the operation of ventilators or cooling pumps. Typically, the condenser heat exchanger is a component where the processes of desuperheating, condensation and, in some applications, also subcooling take place. Especially, the process of desuperheating requires huge heat exchanger surface areas due to the low heat transfer coefficient of the vapor phase. The proposed measure aims to reduce the share of desuperheating in the condenser through injection cooling in front of this component. On the one hand, the condenser surface area can be decreased, reducing investment costs. On the other hand, if the surface area is kept constant, the expander backpressure can be reduced due to the improved heat transfer in the condenser, leading to higher power output of the expansion machine. The present study demonstrates the benefit of this optimization measure with the aid of an experimental investigation that is complemented by a numerical analysis. Keeping the condenser surface constant, the condensation pressure can be decreased by up to 11.1%, by applying this injection cooling and together with R1233zd(E) as the working fluid, This, in turn, leads to an increase in net power output of 7.9% and consequently substantial additional revenue, especially with a large number of full load operation hours.